Health related quality of life in patients with congestive heart failure: comparison with other chronic diseases and relation to functional variables. Issue 3 (1st March 2002) - Juenger, J; Schellberg, D; Kraemer, S; Haunstetter, A; Zugck, C; Herzog, W; Haass, M
Abstract : Objective: To assess health related quality of life of patients with congestive heart failure; to compare their quality of life with the previously characterised general population and in those with other chronic diseases; and to correlate the different aspects of quality of life with relevant somatic variables. Setting: University hospital. Patients and design: A German version of the generic quality of life measure (SF-36) containing eight dimensions was administered to 205 patients with congestive heart failure and systolic dysfunction. Cardiopulmonary evaluation included assessment of New York Heart Association (NYHA) functional class, left ventricular ejection fraction, peak oxygen uptake, and the distance covered during a standardised six minute walk test. Results: Quality of life significantly decreased with NYHA functional class (linear trend: p < 0.0001). In NYHA class III, the scores of five of the eight quality of life domains were reduced to around one third of those in the general population. The pattern of reduction was different in patients with chronic hepatitis C and major depression, and similar in patients on chronic haemodialysis. Multiple regression analysis showed that only the NYHA functional class was consistently and closely associated with all quality of life scales. The six minute walk test and peak oxygen uptake added to the explanation of the variance in only one of the eight quality of life domains (physical functioning). Left ventricular ejection fraction, duration of disease, and age showed no clear association with quality of life. Conclusions: In congestive heart failure, quality of life decreases as NYHA functional class worsens. Though NYHA functional class was the most dominant predictor among the somatic variables studied, the major determinants of reduced quality of life remain unknown.